Chapter Stato d'animo e significato in architettura - Pérez-Gómez, Alberto (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2021)
Explores the role of mood and meaning in architectural experience via the German no-tion of stimmung, relating to the central questions of temperance and harmony in music and architecture. Motor resonance and attunement are under-acknowledged ways that architecture shapes experience. Pedagogical skills that acknowledge the complexity of an embodied and situated consciousness, emphasising qualitative, experiential and em-bodied approaches.